Deep eutectic solvent pretreatment and subsequent saccharification of corncob. (September 2015) - Procentese, Alessandra; Johnson, Erin; Orr, Valerie; Garruto Campanile, Anna; Wood, Jeffery A.; Marzocchella, Antonio; Rehmann, Lars
Highlights: Corncob was pretreated with DES for enhanced enzymatic saccharification. 76% of maximum theoretical sugar yield was achieved. The DESs were able to remove lignin and reduce cellulose crystallinity. The pretreatment might be an alternative to ionic liquid based processes. Abstract: Ionic liquid (ILs) pretreatment of lignocellulosic biomass has attracted broad scientific interest, despite high costs, possible toxicity and energy intensive recycling. An alternative group of ionic solvents with similar physicochemical properties are deep eutectic solvents (DESs). Corncob residues were pretreated with three different DES systems: choline chloride and glycerol, choline chloride and imidazole, choline chloride and urea. The pretreated biomass was characterised in terms of lignin content, sugars concentration, enzymatic digestibility and crystallinity index. A reduction of lignin and hemicellulose content resulted in increased crystallinity of the pretreated biomass while the crystallinity of the cellulose fraction could be reduced, depending on DES system and operating conditions. The subsequent enzymatic saccharification was enhanced in terms of rate and extent. A total of 41 g fermentable sugars (27 g glucose and 14 g xylose) could be recovered from 100 g corncob, representing 76% (86% and 63%) of the initially available carbohydrates.